Relevansi Teori Kriminologi Klasik dalam Mengungkap Kejahatan Modern dan Kriminologi Siber - Muhsin Lambok Ilvira; Nanda Reyriski (Mahesa Research Center, 2026)
This article or writing aims to examine the relevance of classical criminology theory in uncovering the phenomenon of modern crime, including cybercrime which is increasingly rampant. The problem is focused on How classical criminology theory can uncover the characteristics of cybercrime which is transnational, anonymous, and technology-based, and How is the relevance of classical criminology theory in explaining the motives, behavior, and dynamics of Modern Crime, Including the forms of crime that are developing in the digital era?, To approach this problem, the theoretical references from Cesare Beccaria and Jeremy Bentham are used, which emphasize that people commit crimes because they calculate profit and loss (hedonism). Data were collected through library research, by reviewing various theoretical references and relevant research results. This study concludes that classical criminology theory still has an important role in uncovering modern crime, even though the world of crime has undergone significant changes due to the development of digital technology. The basic principles of classical theory such as rationality, free will, and consideration of profit and loss remain relevant to explain the motives and behavior of modern criminals, so that the concept of deterrence is still an applicable approach and the anonymous, cross-border, and highly dependent digital characteristics of technological capabilities make classical theory need to be adapted to suit the current criminal context.